1978
DOI: 10.1093/jnci/60.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Antigens on Rat Liver Cells Transformed In Vitro by Chemical Carcinogens

Abstract: With the use of membrane immunofluorescence and xenogeneic antisera, tumor-specific membrane antigens were detected on rat epithelial-like liver cells transformed in vitro by chemical carcinogens. These antigens were not detected in 10-, 15-, and 19-day rat fetuses. Xenogeneic antisera were produced in rabbits by immunization of the rabbits with cultivated BD rat liver cells transformed by dimethylnitrosamine or N-methyl-N'-nitro-N-nitrosoguanidine. The specific antisera against tumor-associated antigen(s) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the present study the strong reactivity was due to immunization of the antiserum donors with cells bearing surface FCS components which were too strongly bound to be removed by washing. The common antigens observed in earlier studies on carcinogentreated or transformed liver cells (Jype et al, 1973;Yokota et al, 1978) could also be due to adsorbed FCS. Yokota et al (1978) showed no loss of antibody following absorption of antiserum with 20% by volume of FCS, but this procedure was completely inadequate in our studies where two consecutive absorptions with 3-fold volumes of glutaraldehyde-cross-linked FCS were necessary to effect antibody removal.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…In the present study the strong reactivity was due to immunization of the antiserum donors with cells bearing surface FCS components which were too strongly bound to be removed by washing. The common antigens observed in earlier studies on carcinogentreated or transformed liver cells (Jype et al, 1973;Yokota et al, 1978) could also be due to adsorbed FCS. Yokota et al (1978) showed no loss of antibody following absorption of antiserum with 20% by volume of FCS, but this procedure was completely inadequate in our studies where two consecutive absorptions with 3-fold volumes of glutaraldehyde-cross-linked FCS were necessary to effect antibody removal.…”
Section: Resultsmentioning
confidence: 70%
“…The common antigens observed in earlier studies on carcinogentreated or transformed liver cells (Jype et al, 1973;Yokota et al, 1978) could also be due to adsorbed FCS. Yokota et al (1978) showed no loss of antibody following absorption of antiserum with 20% by volume of FCS, but this procedure was completely inadequate in our studies where two consecutive absorptions with 3-fold volumes of glutaraldehyde-cross-linked FCS were necessary to effect antibody removal. In view of the propensity of rat liver cells to incorporate heterologous serum proteins on the cell surface, it is suggested that any future immunological studies on carcinogen-treated cultured liver cells will either have to be carried out in vivo, or new culture methods will have to be devised.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation